Studi Deskriptif Kuantitatif Impulsivity pada Pelaku Gambling Addiction - Tiara Eristina; Rida Yanna Primanita (Pusat riset dan Inovasi Nasional, 2025)
Rapid technological developments have made internet access easier and increased smartphone use, including in Indonesia which occupies fourth place in the world with 160.23 million users. One of the negative impacts is the increase in online gambling which can now be accessed easily. This research aims to explore differences in levels of impulsivity in individuals with various levels of severity of online gambling addiction, using Whiteside and Lynam's (2001) theory of impulsivity. The research method used is descriptive quantitative with data collection techniques using a questionnaire in the form of a Likert scale. The research sample was Padang State University students who were addicted to online gambling, selected using a purposive sampling technique. Data analysis was carried out using the Kruskal-Wallis statistical test. The results showed that there was no significant difference in the level of impulsivity between individuals with mild, moderate and severe levels of gambling addiction (p > 0.05).